The Potential of Digital Games to Support English as the Second Language Learners in Bali - I Gede Made Adi Kerta Yasa; Putu Sri Merta Utami (EduInovasi: Journal of Basic Educational Studies, 2025)
There is continuing attention to the educational value of digital games especially for English language teaching. Despite that, the relationship between digital games and ESL learning is particularly tricky in a society that adapted Confucius education style like in Bali. The Balinese government is becoming increasingly aware of the importance of communicative skills and digital learning in English as a Second Language (ESL) education due to the importance of English communication skills is crucial in their tourism industries. Thus, this study review aimed to map the potential of digital games in supporting Balinese ESL learners’ communication skills. The systematic literature review on an ESL digital games from the similar society that adapted the Confucius learning style has been conducted. The findings indicated that (1). MMORPG games were the most common games found followed by tutorial games in the literatures (2). The tutorial games were often custom-built games; (3). Most of the participants were beginner level ESL learners; (4). The majority of digital games were used to aid vocabulary building and comprehension; (5). The majority literatures objectives were implemented digital games to support ESL learner’s communication; (6). The majority literatures discovered positive impacts on SEA Learners psychology; (7). The digital games are capable to develop ESL learners’ contemporary skills. Taken as whole, these findings suggest the overall suitability of using digital games to aid ESL learners in Bali.